Preliminary Trials for Introductoin of Robinia Pseudo-acacia L. in Middle and Outer Outer Pradesh, Himalayas - Joshi, H. B. (Indian Forester, 1973)
Robinia pseudo-acacia L. (Leguminosae, Papilionatae), due to its multi-purpose use in soil conservation, as a leaf fodder, fuel and medium quality timber, has been used widely as an exotic for planting all over the world in temperate zone. In India it has been planted fairly extensively in Jammu and Kashmir and Hamachal, hut in U.P. hills, it has been tried only sporadically on road-sides and compounds. Attempts to raise it gave only partial success for some years, and only in past 2-3 years encouraging results have been achieved in a few localities like Lohaghat in Pithoragarh Forest Division, Korwa in Chakrata Forest Division and Gaja in Nainital Forest Division. The article gives an account of sites and trial plantations, Forest to identify characteristics of sites where success has been achieved and gives outline of programme for future in extending the trial of this species which can be of real benefit to local economy. Robinia pseudo-acocia L. (Leguminosae, Papilionaceae), variously called as Black Locust, False Acacia or simply Robinia. is a native of Appalachian mountains of eastern North America, It is a medium-sized, handsome tree, growing to a height of about 24 metres. The species belongs to tile summer rainfall zone of the U.S.A., with an annual rainfall range of 1000 to 1375 mm and a mean annual temperature of 10 to 16Â°C. It is a pioneering species there, coming naturally on abondoned farm land. It suckers freely and regenerates easily from seed as. well as coppice. It is extensively used in soil conservation, as a soil stabilizer and improver in the afforestation of barren land.